Structural evolution of reduced GeOx nanoparticles. Issue 4 (13th January 2017) - McLeod, John A.; Zhao, Jia; Yang, Linju; Liu, Yi; Liu, Lijia
Abstract : GeO x nanoparticles are studied using soft X-ray spectroscopy, revealing the influence of preparation conditions on the structure and composition. Abstract : GeO x nanoparticles (NPs) are of growing interest in lithium storage and optoelectronics. GeO x NPs prepared by chemical reduction, exposed to air or retained under N2, then annealed under H2 at various temperatures are studied herein using soft X-ray spectroscopy. We find that fresh and air-exposed GeO x NPs evolve rather differently under annealing. The fresh GeO x NPs start as a very amorphous heterogeneous mixture of GeO x and Ge, and during annealing both the valence band and conduction band edges evolve. In contrast, the air-exposed GeO x NPs initially contain quartz-phase GeO2, and during annealing only the conduction band edge evolves due to increased oxygen vacancies forming unoccupied defect states (the valence band does not change until annealing at high temperture, at which point almost all of the GeO2 is removed). These findings suggest a preparation and annealing strategy that could be used to tailor GeO x NPs for their intended use in lithium storage or optoelectronic applications.